Rutting Resistance of full depth Asphalt Pavement Structure - Hawraa M. jaffer; Hasan H. Joni; Rasha H. Al-Rubaee (Migration Letters, 2023)
Asphalt roads that have been permanently deformed have a negative effect on their performance. The pavement’s service life is shortened and dangers to motorists and pedestrians are increased when rusting occurs. defects in the pavement, such as rutting and fatigue, The ability of an asphalt pavement structure to withstand rutting depends on the high-temperature properties of the asphalt mixture, as well as the pavement’s structure and thickness. In this study, a full-depth wheel tracking test is utilized to examine the effects of full-depth asphalt layers and the addition of RAP on rutting resistance by implementing models of two layers of full-depth asphalt pavement structure (surface, base) layer with 30% RAP, This paper’s findings shown that asphalt mixtures including RAP can achieve high levels of rutting performance of full-depth by using model with a dimension (30cm* 30cm * 15cm). According to the findings, recycled asphalt pavement performs better than the original. It can be noticed that at an optimum value of about 30% RAP will reduce the rutting depth by (60%), at temperatures of 60 °C.